SPECIES COMPOSITION AND DISTRIBUTION OF PEANUT PESTS IN UZBEKISTAN - Khakimov , Bakhodir Absamatovich; Sodiqova , Dilfuza G‘afforovna (Educational Research in Universal Sciences, 2023)
Peanut pests are widespread throughout the world, but few of them are of regional economic importance. This article briefly discusses leaf pests, stem pests, root pests of peanuts, the harmfulness of peanuts, and their economic importance.